IoT sensing networks for gait velocity measurement - Chou, Jyun-Jhe; Shih, Chi-Sheng; Wang, Wei-Dean; Huang, Kuo-Chin (Zielona Góra: Uniwersytet Zielonogórski)
Gait velocity has been considered the sixth vital sign. It can be used not only to estimate the survival rate of the elderly, but also to predict the tendency of falling. Unfortunately, gait velocity is usually measured on a specially designed walk path, which has to be done at clinics or health institutes. Wearable tracking services using an accelerometer or an inertial measurement unit can measure the velocity for a certain time interval, but not all the time, due to the lack of a sustainable energy source.
Keywords: Internet of Things (IoT); middleware; compression; data fusion; data reduction